2021
DOI: 10.7759/cureus.20163
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Clinical Efficacy of Micro-Focused Ultrasound Treatment for Skin Rejuvenation and Tightening

Abstract: The demand for non-invasive skin-tightening techniques is continuously on the rise, as now numerous patients seek safe and effective alternative body, neck, and facial aesthetic surgical procedures. Microfocused ultrasound (MFU) has been recently introduced as a novel energy modality for skin rejuvenation to produce a more significant wound healing response at various levels, including strong collagen remodeling and long-lasting clinical response. This literature study was intended to find the role and efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 22 publications
1
22
0
3
Order By: Relevance
“…Ulthera® generates energy in short duration range of 25–50 ms with high frequencies of 4, 7, and 10 MHz propagating to an approximate focal depth of 4.5 , 3.0 , and 1.5 mm to create thermal coagulation in different skin layers 9,10 . Specifically, the 4.5 mm transducer is used to target the SMAS, whereas the 3.0 mm and 1.5 mm transducers target the collagen and elastin in the dermis layer of the skin 9,11–13 . Likewise, the intense focused US device, such as Doublo™, HIRONIC Co. applying 4 MHz, 4.5 mm probe and 7 MHz 3.0 mm probe also showed the efficacy in lower face and neck skin laxity correction 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ulthera® generates energy in short duration range of 25–50 ms with high frequencies of 4, 7, and 10 MHz propagating to an approximate focal depth of 4.5 , 3.0 , and 1.5 mm to create thermal coagulation in different skin layers 9,10 . Specifically, the 4.5 mm transducer is used to target the SMAS, whereas the 3.0 mm and 1.5 mm transducers target the collagen and elastin in the dermis layer of the skin 9,11–13 . Likewise, the intense focused US device, such as Doublo™, HIRONIC Co. applying 4 MHz, 4.5 mm probe and 7 MHz 3.0 mm probe also showed the efficacy in lower face and neck skin laxity correction 14 .…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Specifically, the 4.5 mm transducer is used to target the SMAS, whereas the 3.0 mm and 1.5 mm transducers target the collagen and elastin in the dermis layer of the skin. 9,[11][12][13] Likewise, the intense focused US device, such as Doublo™, HIRONIC Co. applying 4 MHz, 4.5 mm probe and 7 MHz 3.0 mm probe also showed the efficacy in lower face and neck skin laxity correction. 14 However, some complications from MFUs have been reported in those conventional transducers.…”
Section: Ta B L E 2 Mean Depression Volume and Mean Depression Volume...mentioning
confidence: 99%
“…They determined that MFU yielded significant improvements in the aging face. 42 They highlight a prospective study by Lu et al of 25 patients who underwent MFU (level 3 evidence) that showed a significant decline in mean wrinkles score after 3 months (p ¼ 0.0222). However, while a 0.47 mm brow lift was also seen at 3 months, this returned to baseline after 6 months.…”
Section: Energy-based Facial Rejuvenationmentioning
confidence: 94%
“…The reason for these findings is the thermal action of HIFU on the fibrous tissue constituting the SMAS ("lifting effect"), as well as on the collagen of the reticular dermis Despite the remarkable immediate effect on the skin, HIFU has proven to be even more efficient in the long term. Authors [18] reported that the interval for a reevaluation, in order to judge the results, may vary from 2 to 6 months; however, Suh et al (2016) [19] treated individuals with a total of 3 sessions of Focused Ultrasound with intervals of 4 weeks between sessions.…”
Section: F S Borges Et Almentioning
confidence: 99%
“…The distance between the lines of TCPs ranges from 2 to 5 mm [18]. This might be adjusted to make with it occurs automatically during the delivery of TCPs using "multiline" transducers, but with the use of "single-line" transducers.…”
Section: F S Borges Et Almentioning
confidence: 99%